Lyapunov-based missile terminal guidance with short time convergence considering seeker's first-order lag. (August 2017) - Zheng, Duo; Lin, Defu; Xu, Xinghua; Cheng, Zhenxuan
This paper presents a novel guidance law considering the seeker dynamics for manoeuvring targets to achieve short homing time guidance using the Lyapunov method. Based on linear and nonlinear kinematics, a Lyapunov-based guidance law is synthesised to compensate for the seeker's first-order lag. The closed-form solution of the proposed guidance system is also derived analytically. To implement the proposed guidance law, a Kalman filter algorithm is presented to extract the line-of-sight rate and its higher order derivative. Numerical simulations are carried out to demonstrate the effectiveness of the proposed guidance law under various conditions. Monte Carlo simulations are also performed to test the robustness against measurement noise.